(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The current research aims to identify the role of classroom activities in developing some life skills in science from the point of view of teachers,The researcher used the descriptive approach, and prepared a questionnaire of( 31) items for this purpose, The research was applied during the first semester of the academic year 2020 2021.The sample of the study was (100) teachers . The results of the research showed that the role of classroom activities in developing some life skills in science from the point of view of teachers came to a high degree, It was also found that there were no statistically significant differences between the averages of teachers answers about the role of classroom activities in developing life skills according to ( gender- number of years of experience), while there were statistically significant differences according to the academic and educational qualification variable in favor of for the holders of the university degree (class teacher). The research also presented several proposals, including: moving away from traditional teaching methods in which the student is passive and paying attention to teaching methods that depend on the positive participation of students, enhancing life skills in science curricula and others, providing the school with encouraging incentives for creative supervisors on classroom activities, which leads to teacher strengthening. And increase its effectiveness towards exercise.